MAJORITY HEGEMONY IN A MULTICULTURAL SOCIETY - Wazdy, Salim; Ningsih, Tutuk; Yahya, Muhamad Slamet (Jurnal Kajian Pendidikan dan Psikologi, 2024)
This research aims to explore the concept of majority hegemony in a multicultural society, with a focus on the dynamics of interaction between majority and minority groups. Through a qualitative approach and case study method, this research explores the perspectives of community and religious figures who represent both groups in a multicultural society. Data analysis was carried out by paying attention to the concept of hegemony in the theories of political sociology and ethnic conflict. The research results underscore the various manifestations of majority hegemony in daily life, encompassing public policies, cultural practices, and social dynamics. The implications of these findings are discussed in the context of a better understanding of the challenges and opportunities in building a society that is inclusive and just for all groups.